Colestasis intrahepática en embarazo de 38 semanas - Limones Sánchez, Cynthia Elizabeth (2020)
Intrahepatic cholestasis of pregnancy is a disease that occurs in women during pregnancy. It is a condition that affects the release of bile (a digestive juice) from the liver cells. Bilirubin accumulates affecting liver function. Symptoms usually begin in the third trimester of pregnancy and may include itching. Occasionally, the skin and the white part of the eyes may have a yellowish color (jaundice). In addition, there are risks to the developing baby, such as premature delivery and stillbirth. In about 15% of cases the disease is caused by alterations (mutations) in the ABCB11 or ABCB4 genes. Mutations in the ABCB11 and ABCB4 genes are inherited in an autosomal dominant manner. However, in most cases (about 75%) the cause is unknown. Symptoms only occur in pregnancy and problems occur after delivery, but may return during subsequent pregnancies.